2019
DOI: 10.1021/acsomega.9b01701
|View full text |Cite
|
Sign up to set email alerts
|

Charge Accumulation, Recombination, and Their Associated Time Scale in Efficient (GUA)x(MA)1–xPbI3-Based Perovskite Solar Cells

Abstract: Here, we study the influence of guanidinium (GUA) ions on the open-circuit voltage (Voc) in the (GUA)x(MA)1–xPbI3 based perovskite solar cells. We demonstrate that incorporation of GUA forms electronic and ionic accumulation regions at the interface of the electron transporting layer and perovskite absorber layer. Our electrochemical impedance spectroscopy results prove that the formed accumulation region is associated with the enhanced surface charge capacitance and photovoltage. Furthermore, we also demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…In our previous reports on GUA x MA 1Àx PbI 3 PSCs, we observed a complex impedance peak between 10 5 and 10 6 Hz and the corresponding time constant depicts the recombination kinetics in the cell, which is significantly suppressed upon GUA incorporation. 43,48 However, such high-frequency response is not observed in the present study. In turn, we observed that with incorporation of a small amount of the GUA cation in the MAPbI 3 crystal structure, the rate of change in the apparent time constant is significantly suppressed with a change in temperature.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…In our previous reports on GUA x MA 1Àx PbI 3 PSCs, we observed a complex impedance peak between 10 5 and 10 6 Hz and the corresponding time constant depicts the recombination kinetics in the cell, which is significantly suppressed upon GUA incorporation. 43,48 However, such high-frequency response is not observed in the present study. In turn, we observed that with incorporation of a small amount of the GUA cation in the MAPbI 3 crystal structure, the rate of change in the apparent time constant is significantly suppressed with a change in temperature.…”
Section: Resultscontrasting
confidence: 84%
“…41,42 Surprisingly, it was found that the incorporation of GUA in the MAPbI 3 perovskite structure enhances the hysteresis effect in comparison to the pristine MAPbI 3 based PSCs. 38,43 Initially, Yang et al assumed that GUA is not confined within the perovskite lattice but rather is weakly hydrogen-bonded to the under-coordinated ionic species mainly at grain boundaries. 38 They proposed that mobile GUA cations can migrate to the interfaces and screen the applied electric field leading to enhanced hysteresis in the device.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the introduction of GA + to 2D perovskite not only increased the charge transport and diffusion length, but also formed an accumulation region of electrons and ions on the surface between the electron transport layer and the perovskite light‐absorbing layer, which led to an increase in V OC . [ 154 ]…”
Section: D Perovskite‐based Solar Cellsmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have become the front runner in emerging thin-film solar cells, with power conversion efficiency (PCE) exceeding 25% owing to their low-cost solution processing and exciting optoelectronic features such as their high absorption coefficient, tunable stability, and superior carrier transportation properties [1][2][3][4][5][6][7][8]. Nevertheless, the key issue that hampers the commercialization of PSCs is device instability under light, moisture, and high-temperature exposure [9,10].…”
Section: Introductionmentioning
confidence: 99%